Uncovering the Hidden Effort Problem - BEN‐REPHAEL, AZI; CARLIN, BRUCE I.; DA, ZHI; ISRAELSEN, RYAN D. (Journal of Finance, 2025)
ABSTRACT We analyze minute‐by‐minute Bloomberg online status and study how the effort provision of executives in public corporations affects firm value. While executives spend most of their time doing other activities, patterns of Bloomberg usage allow us to characterize their work habits as measures of effort provision. We document a positive effect of effort on unexpected earnings and cumulative abnormal returns following earnings announcements, and a reduction in credit default swap spreads. This is robust to using exogenous weather patterns as an instrument. Long‐short, calendar‐time effort portfolios earn significant average daily returns. Finally, we revisit important agency issues from the literature.